Hedging Devices in ‘Monavie Juice’ Testimony - Nurdiana Nurdiana (Journal of English Language and Culture, 2017)
Culture has a significant influence on how people treat illnesses. Indonesians, for example, believe that traditional healing can help them cure their illnesses. One of the traditional or alternative healing booming in Indonesia is a drink made of fruit or vegetables. This kind of drink is called juice. To convince people that juice is effective enough to cure an illness and to persuade people to buy the product, persuasive testimony is needed. Linguisctically, when discussing persuasive texts, we can relate them to powerful and powerless language. According to Blankenship and Holtgraves (2005: 4), powerless language refers to the use of linguistic features such as tag questions, hesitations, disclaimers, hedges, polite forms, etc. in a text, while powerful language does not denote these features. Hedges can be words like probably, kind of, sort of, and possibly (Carli, 1990; Gibbons, Busch, & Bradac, 1991; Holtgraves & Lasky, 1999; Hosman, 1989; Hosman, Huebner, & Siltamen, 2002 cited in Durik, Britt, Reynolds, and Storey, 2008: 218). Hedges can also be words like approximately, roughly, somewhat, quite, often, or occasionally (Salager-Meyer, 1994: 154). This paper shall discuss what hedges appear in ‘Monavie or Acai Active Blend Juice’ testimony as there are many types of hedges used in different discourse. Keywords: Culture, persuasive testimony, hedging device